Fatigue and declines in cognitive functioning in multiple sclerosis. - Krupp, L B; Elkins, L E (Neurology)
Objective: To determine whether cognitive fatigue, defined as a decline in cognitive performance over a single testing session, could be identified in MS.Methods: Forty-five individuals with MS and 14 healthy control participants completed a 4-hour session of cognitive testing that involved a baseline neuropsychological battery, a continuous effortful cognitive task (completing mental arithmetic problems administered on a computer), and a repeat neuropsychological battery. Self-report measures of fatigue and affect were completed before each step of the testing session.Results: The pattern of change in cognitive performances over the testing session significantly differed between the MS and control participants. Individuals with MS showed declines on measures of verbal memory and conceptual planning, whereas the control participants showed improvement. Although there were no significant differences between the groups on any of the baseline cognitive measures, the MS participants performed worse than the control subjects on tests of visual memory, verbal memory, and verbal fluency that were repeated following the continuous effortful cognitive task. Both MS and control participants reported increased mental and physical fatigue across the testing session compared with their baseline values.Conclusion: Individuals with MS show declines in cognitive performance during a single testing session and fail to show the improvement exemplified by healthy control subjects.